The Azulene Framework as a Novel Arene Bioisostere: Design of Potent Dopamine D4 Receptor Ligands Inducing Penile Erection - Löber, Stefan; Tschammer, Nuska; Hübner, Harald; Melis, Maria Rosaria; Argiolas, Antonio; Gmeiner, Peter (ChemMedChem, 2009)
(Graph Presented) Blue makes it happen: The non-uniform charge distribution of the blue colored azulene framework is highly suitable for the bioisosteric replacement of bicyclic heteroarene moieties. Showing an analogous binding mode as heterocyclic dopamine D4 receptor-selective lead compounds, the induction of penile erection in rats over a greater range of doses indicates a putative advantage of the rationally developed azulene derivative 2 b over apomorphine. © 2009 Wiley-VCH Verlag GmbH& Co. KGaA.
UnivIS-Import:2015-03-09:Pub.2009.nat.dchph.lphch.theazu
Keywords: Agonists; Azulenes; Bioisosteres; Dopamine D4 receptors; GPCR; Penile erection